Reaction and Mechanistic Studies of Heterogeneous Hydroamination over Support‐Stabilized Gold Nanoparticles. Issue 19 (14th September 2016) - Sengupta, Manideepa; Bag, Arijit; Das, Subhasis; Shukla, Astha; Konathala, L. N. Sivakumar; Naidu, C. A.; Bordoloi, Ankur
Abstract: Highly stable gold nanoparticles (GNPs) around 5–6 nm have been prepared by in situ reduction of chloroauric acid on the surface of nitrogen‐rich mesoporous carbon (MCN) without adding any extra stabilizing agent. The synthesized materials have been efficiently utilized as a catalyst for the truly heterogeneous hydroamination of phenylacetylene with aniline. Large turnover numbers (42×10 6 ) were achieved by suitably adjusting the gold/support (w/w) ratio, time, temperature, and solvent, leading to 98 % selectivity towards the Markovnikov product. Density functional theory (DFT) studies have been performed to predict the mechanistic pathway of hydroamination with Au 0 in GNP@MCN. To understand the structure–activity relationship, the catalyst was characterized by using different techniques such as X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen physisorption studies (BET), X‐ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy. Abstract : Au hydroamination catalyst : The in situ synthesis of gold nanoparticles in the surface cavity of mesoporous nitrogen‐rich carbon (MCN) allowed them to be utilized efficiently as a catalyst in the hydroamination of phenylacetylene with aniline, with more than 98 % selectivity towards the Markovnikov addition product. The mechanistic pathway has been studied with DFT‐based calculations, which predict the stabilization of tetranuclear Au clusters over the MCN support.